Expression and co-location of prohibitin genes in salt-tolerance QTLs in rice (Oryza sativa) - Rakesh Bhowmick; Sushma Tiwari; Vandana Rai; Nagendra Kumar Singh (The Indian Journal of Agricultural Sciences, 2020)
Prohibitin proteins are involved in diverse biological functions including cell cycle regulation, mitochondrial activity, apoptosis, hormonal signalling and so on. Prohibitin family genes are conserved across the life taxa in both eukaryotes and prokaryotes. An experiment was conducted at ICAR-National Institute for Plant Biotechnology, New Delhi (2018-19) in which we identified 19 prohibitin genes present on 10 different chromosomes of the ‘Nipponbare’ reference rice (Oryza sativa L.) genome and analysed their possible role in salt tolerance, as they are known to regulate ion channels in plant and animal cells. A protein sequence based neighbour joining phylogentic tree clustered these 19 genes into three groups. Digital gene expression analysis revealed the highest level of expression of the prohibitin genes in anthers and radicle tips. Nine of these prohibitin genes were co-located in the salt-tolerance QTL regions of the rice genome, three of which (LOC_Os01g40560, LOC_Os03g60000 and LOC_Os08g15600) were significantly upregulated in response to salt stress in the tolerant genotype. These prohibitin genes are strong candidates for improving salt-tolerance in rice through marker-assited rice breeding after validation.